Syarī’ah Audit Practices at Zakāt Institutions in Indonesia: In the Legal Perspectives - Amelia, Erika; Darwanto, Darwanto; Zakiyudin, Muhammad Ali; Yusup, Mohammad (Faculty of Sharia and Law, UIN Syarif Hidayatullah Jakarta, 2023)
Abstract. The practice of Syarī'ah audits at Zakāt institutions in Indonesia has been effective since 2020 through the Decree of the Minister of Religion Number 606 of 2020. In practice, Syarī'ah audits play a role as guarantee and quality control for the implementation of ZIS and DSKL fund management. T his study aims to analyze the practice of Shari'ah auditing at Zakāt institutions in Indonesia from the perspective of positive law and Shari'ah. This study uses a descriptive qualitative approach through analysis of the contents of regulations, data, and documents. The results of the study show that from a legal perspective, the process of managing funds and governance of ZIS and DSKL has not been regulated in positive law and in Shari'ah law. The solution that has been carried out by Shari'ah auditors so far is through the process of priority legal and fiqh istinbāth (ijtihad al-ahkamil-ahkam).Abstrak. Praktik audit Syarī’ah pada lembaga Zakāt di Indonesia telah efektif sejak tahun 2020 melalui Keputusan Menteri Agama Nomor 606 Tahun 2020. Dalam penerapannya, audit Syarī’ah berperan sebagai penjaminan dan pengendalian mutu pelaksanaan pengelolaan dana ZIS dan DSKL. Penelitian ini bertujuan untuk menganalisis praktik audit Syarī’ah pada lembaga Zakāt di Indonesia dari perspektif hukum positif dan Syarī’ah. Penelitian ini menggunakan metode deskriptif dengan pendekatan kualitatif deskriptif melalui analisis isi peraturan, data, dan dokumen. Hasil penelitian menunjukkan bahwa dari segi hukum, proses pengelolaan dana dan tata kelola ZIS dan DSKL belum diatur dalam hukum positif yang berjalan dan dalam hukum Syarī’ah. Solusi yang dilakukan auditor Syarī’ah selama ini adalah melalui proses istinbāth hukum dan fiqh prioritas (ijtihad al-ahkamil-ahkam).